Religious Considerations In Educational Policy In A Multicultural Society - Asrop Syafi’i; Nur ‘Azah; Mardiyah; Muhammad Yusron Maulana El-yunusi; Muh Ibnu Sholeh (International Journal of Education Management and Religion, 2024)
This study aims to analyze the role of religious considerations in educational policies within a multicultural society, focusing on how educational policies can accommodate religious and cultural diversity in communities with different social and religious backgrounds. Multicultural societies face challenges in creating educational policies that can fairly include all religious groups, without prioritizing one religion or culture over others. Therefore, this research focuses on how educational policies can be structured to create an inclusive education system that is sensitive to religious diversity. The study uses a library research method, collecting and analyzing relevant literature on religious education policies in multicultural countries such as Indonesia, India, and European nations. Through this approach, the author explores information about the implementation of educational policies that consider religious diversity and their impact on social integration. The findings indicate that religious education policies, when properly designed, can be an effective tool to strengthen tolerance and social integration in multicultural societies. However, to achieve this goal, policies must carefully consider the rights of minority groups to prevent discrimination. Educational policies should also undergo regular evaluations and adjustments to ensure inclusivity and equality for all religious groups in education.